First-line avelumab treatment in patients with metastatic Merkel cell carcinoma: 4-year follow-up from part B of the JAVELIN Merkel 200 study - D'Angelo, Sandra P.; Lebbé, C.; Mortier, L.; Brohl, A. S.; Fazio, N.; Grob, J. -J.; Prinzi, N.; Hanna, G. J.; Hassel, Jessica C.; Kiecker, F.; von Heydebreck, A.; Güzel, G.; et al. (ESMO open, 2024)
Background - Results from the JAVELIN Merkel 200 study led to the approval of avelumab [an anti-programmed death-ligand 1 (PD-L1) antibody] for the treatment of metastatic Merkel cell carcinoma (mMCC) in multiple countries and its inclusion in the treatment guidelines as a preferred or recommended therapy in this setting. Here, we report 4-year follow-up results from the cohort of patients with mMCC who received avelumab as first-line treatment. - Patients and methods - In part B of JAVELIN Merkel 200, a single-arm, open-label, phase II study, patients with mMCC who had not received prior systemic therapy for metastatic disease received avelumab 10 mg/kg via intravenous infusion every 2 weeks until confirmed disease progression, unacceptable toxicity, or withdrawal. In this analysis, long-term overall survival (OS), patient disposition, and subsequent treatment were analyzed. - Results - In total, 116 patients received first-line avelumab. At the data cutoff (2 February 2022), the median follow-up was 54.3 months (range 48.0-69.7 months). Seven patients (6.0%) remained on treatment and an additional 21 patients remained in follow-up (18.1%); 72 patients (62.1%) had died. The median OS was 20.3 months [95% confidence interval (CI) 12.4-42.0 months], with a 4-year OS rate of 38% (95% CI 29% to 47%). In patients with PD-L1+ or PD-L1− tumors, the 4-year OS rate was 48% (95% CI 26% to 67%) and 35% (95% CI 25% to 45%), respectively. In total, 48 patients (41.4%) received poststudy anticancer drug therapy, most commonly etoposide (20.7%), carboplatin (19.0%), and avelumab (12.1%). - Conclusions - Avelumab first-line monotherapy in patients with mMCC resulted in meaningful long-term OS, which compared favorably with historical studies of first-line chemotherapy. These results further support the role of avelumab as a standard of care for patients with mMCC.